Cagayan de Oro Convention and Exhibition Complex - Celis, Aedriane G.
Meeting places are not new forms of spaces in society, nor is a convention center an unfamiliar structure in the urban fabric of a city. However, elevating both these variables in society could set an unconventional environment. Architecture has currently been exploring beyond boundaries and innovating trends that set design above the normative. This thesis inculcates those perspectives to create an integrated convention and exhibition complex to foster transparency and break compartmentalization of spaces. In the pages below, you will see how convention centers architecture could evolve into more than meeting utilitarian boxes and can relate and create an impact in all levels of society, cultural, social and economic. These three said aspects are also carried largely by tourism and by putting them together in an integrated way as is in explored with the design of the CDO Convention and Exhibition Complex, thus resulting into something different.